2020
DOI: 10.1002/mnfr.202000797
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol Acetate Improves the Cognitive Function of APP/PS1 Transgenic Mice in ERβ‐dependent Manner

Abstract: ScopeAlzheimer's disease (AD) is the most prevalent form of dementia in the aging population; however, no effective therapy has been established. It has been previously demonstrated that daily intake of hydroxytyrosol (HT), a polyphenol in olive oil, at a daily dietary level mildly improves cognition in AD mice. In the present study, HT acetate (HT‐ac), which is a natural derivative of HT in olive oil that exhibits better bioactivity than HT improves cognition.Methods and ResultsHT‐ac to APP/PS1 is orally admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…[36][37][38] HTA-enriched functional foods could have neuroprotective, anticoagulant, arthritis preventive and other health-promoting properties. [4,8,39,40] For example, olive oil that contains 250 mg kg À 1 hydroxytyrosol derivatives can be called healthpromoting according to an EU regulation (EU Commission Regulation No. 432/2012).…”
Section: Chembiochemmentioning
confidence: 99%
See 2 more Smart Citations
“…[36][37][38] HTA-enriched functional foods could have neuroprotective, anticoagulant, arthritis preventive and other health-promoting properties. [4,8,39,40] For example, olive oil that contains 250 mg kg À 1 hydroxytyrosol derivatives can be called healthpromoting according to an EU regulation (EU Commission Regulation No. 432/2012).…”
Section: Chembiochemmentioning
confidence: 99%
“…The phenols of olives have several healthpromoting properties, e. g., neuroprotective, which are associated with their antioxidant and anti-inflammatory benefits. [4][5][6][7][8] Several methods have been developed to facilitate the degradation or extraction of phenolic compounds, such as chemical oxidation, solvent extraction, membrane systems or adsorbents. [9][10][11][12][13][14][15][16][17][18][19][20] However, all these systems require several laborious steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, AβOi-induced abnormalities in PI3K/Akt1, ERK/MAPK/RSK2, JAK2/STAT3, and JNK/p38 signaling pathways were reversed by HT. A recent study also reported that oral administration of HT acetate (50 mg/kg) into APP/PS1 mice for 3 months (from 3.5 to 6.5 months old) attenuated apoptosis in the cortex and hippocampus and improved cognitive function, measured using T-maze and MWM tests [ 29 ].…”
Section: Small Molecules With Protective Activity Against Aβo Neurotoxicitymentioning
confidence: 99%
“…The promising pharmacological activities of hydroxytyrosol (as cardioprotective, anticancer, neuroprotective and antimicrobial agent) have been recently reviewed [ 79 , 244 ]. Analogously, hydroxytyrosol acetate (2-(3,4-dihydroxyphenyl)ethylacetate), a diphenolic constituent of olive oil, is characterized by peculiar biological activities [ 245 , 246 , 247 , 248 ]. Several hydroxytyrosol derivatives have been explored over the past decades, to extend its biological applications [ 249 , 250 , 251 , 252 ].…”
Section: Diphenolsmentioning
confidence: 99%